2014
DOI: 10.1021/ja407527p
|View full text |Cite
|
Sign up to set email alerts
|

Probing the N-Terminal β-Sheet Conversion in the Crystal Structure of the Human Prion Protein Bound to a Nanobody

Abstract: Prions are fatal neurodegenerative transmissible agents causing several incurable illnesses in humans and animals. Prion diseases are caused by the structural conversion of the cellular prion protein, PrP(C), into its misfolded oligomeric form, known as prion or PrP(Sc). The canonical human PrP(C) (HuPrP) fold features an unstructured N-terminal part (residues 23-124) and a well-defined C-terminal globular domain (residues 125-231). Compelling evidence indicates that an evolutionary N-terminal conserved motif … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
125
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 65 publications
11
125
0
Order By: Relevance
“…In vitro, Nb484 is able to slow down the aggregation into fibrils of murine MoPrP(23e230) in the presence of preformed murine PrP Sc seeds; the lag phase of aggregation kinetics is indeed extended by a factor~2 (~75 h versus 30 h in the presence and absence of Nb484, respectively) [125]. Moreover, Nb484 also inhibits the prion propagation in vivo: scrapie infected murine cells (ScGT1) treated with Nb484 show decreased PrP Sc levels compared to non-treated cells, the effect being Nb484 dose-dependent.…”
Section: Nb484 and Priov3 As Mechanistic Probesmentioning
confidence: 99%
See 3 more Smart Citations
“…In vitro, Nb484 is able to slow down the aggregation into fibrils of murine MoPrP(23e230) in the presence of preformed murine PrP Sc seeds; the lag phase of aggregation kinetics is indeed extended by a factor~2 (~75 h versus 30 h in the presence and absence of Nb484, respectively) [125]. Moreover, Nb484 also inhibits the prion propagation in vivo: scrapie infected murine cells (ScGT1) treated with Nb484 show decreased PrP Sc levels compared to non-treated cells, the effect being Nb484 dose-dependent.…”
Section: Nb484 and Priov3 As Mechanistic Probesmentioning
confidence: 99%
“…It was chosen among 14 nanobodies because it displayed the highest affinity for recombinant human PrP (HuPrP (23e231) and HuPrP (90e231)) [125]. Its epitope is discontinuous and includes residues 123e125, the b2-a2 loop (residues 164e170) and half of the a2-helix (residues 174e185) (Fig.…”
Section: Prp Specific Nanobodies Nb484 and Priov3: Generation And Chamentioning
confidence: 99%
See 2 more Smart Citations
“…2,48 The structural information on the disordered N-terminal prion protein region has also been elucidated by a VHH-inhibiting prion oligomerization, eventually contributing to the understanding of early prion formation. 2,49 Similarly, crystallization process of components of bacterial type 2 secretion system demonstrated that the VHHs could substantially facilitate well-diffracting crystal formation by merely providing additional contact surface to the target proteins. 2,50,51 By an elegantly experimental design, another example of the use of nanobody is to trigger the depletion of antigen via the ubiquitin pathway.…”
mentioning
confidence: 99%